Review of Networks of Faith & Profit: Monks, Merchants, and Exchanges between China and Japan, 839–1403 CE by Yiwen Li, Cambridge and New York: Cambridge University Press, 2023. xvi + 211 - Heine, Steven (Silva Iaponicarum, 2024)
Review of Networks of Faith & Profit: Monks, Merchants, and Exchanges between China and Japan, 839–1403 CE by Yiwen Li, Cambridge and New York: Cambridge University Press, 2023. xvi + 211